Masa Depan Manajemen Hubungan Manusia: Tren, Pengaruh Teknologi, dan Strategi Adaptasi - Hamdan; Casyudi Firdaus; Dede Nursyamsy; Efrita Norman (MES Management Journal, 2024)
This research examines future trends and developments in human relations management (HRM), particularly in the context of technology, workforce diversification, as well as the strategies that organizations must adopt to face these challenges. Using literature study methods, this research identifies major changes in HRM, such as the use of artificial intelligence (AI) in recruitment and performance management processes, as well as the increasing popularity of remote work post the COVID-19 pandemic. This research also highlights the ethical challenges that arise from the use of technology in HRM, including the potential for algorithmic bias and unfairness in decision making. The results of this research suggest strategies for sustainable employee skills development, creating an inclusive work culture, and ethical technology integration to support organizational sustainability in the future. This research makes an important contribution to the literature highlighting the long-term impact of technology adoption in HRM as well as offering practical recommendations for organizations in facing global change.